Anticancer potential of sanguinarine for various human malignancies. (June 2017) - Achkar, Iman W; Mraiche, Fatima; Mohammad, Ramzi M; Uddin, Shahab
Sanguinarine (Sang) – a benzophenanthridine alkaloid extracted from Sanguinaria canadensis – exhibits antioxidant, anti-inflammatory, proapoptotic and growth inhibitory activities on tumor cells of various cancer types as established by in vivo and in vitro studies. Although the underlying mechanism of Sang antitumor activity is yet to be fully elucidated, Sang has displayed multiple biological effects, which remain to suggest its possible use in plant-derived treatments of human malignancies. This review covers the anticancer abilities of Sang including inhibition of aberrantly activated signal transduction pathways, induction of cell death and inhibition of cancer cell proliferation. It also highlights Sang-mediated inhibition of angiogenesis, inducing the expression of tumor suppressors, sensitization of cancer cells to standard chemotherapeutics to enhance their cytotoxic effects, while addressing the present need for further pharmacokinetic-based studies.